Drought reduced monoterpene emissions from the evergreen Mediterranean oak Quercus ilex: results from a throughfall displacement experiment - a.-V. Lavoir; Staudt, M; Schnitzler, J P; Landais, D; Massol, F; Rocheteau, A; Rodriguez, R; Zimmer, I; Rambal, S (Biogeosciences, 2009)
The effects of water limitations on the emission of biogenic volatile organic compounds are not well understood. Experimental approaches studying drought effects in natural conditions are still missing. To address this question, a throughfall displacement experiment was set up in a natural forest of Quercus ilex, an evergreen Mediterranean oak emitting monoterpenes. Mature trees were exposed in 2005 and 2006 either to an additional drought, to irrigation or to natural drought (untreated control). In both years, absolute monoterpene emission rates as well as the respective standard factors of the trees exposed to normal and additional drought strongly declined during the drought periods. Monoterpene emissions were lower in year 2006 than in year 2005 (factor 2) due to a more pronounced summer drought period in this respective year. We observed a signiﬁcant difference between the irrigation and additional drought or control treatment: irrigated trees emitted 82% more monoterpenes during the drought period 2006 than the trees of the other treatments. However, no signiﬁcant effect on monoterpene emission was observed between normal and additional drought treatments, despite a signiﬁcant effect on leaf water potential and photochemical efﬁciency. During the development of drought, monoterpene emissions responded exponentially rather than linearly to decreasing leaf water potential. Emissions rapidly declined when the water potential dropped below −2 MPa and photosynthesis was persistently inhibited. Monoterpene synthase activities measured in vitro showed no clear reduction during the same period. From our results we conclude that drought signiﬁcantly reduces monoterpene ﬂuxes of Mediterranean Holm oak forest into the atmosphere due to a lack of primary substrates coming from photosynthetic processes
Keywords: BVOC emission; Drought; Quercus ilex (voyant); Water availability